Rancang Bangun Sistem Aplikasi Pembelajaran Pada Min Toweren - Husna Gemasih; Laili Wahyunita (INTEGER: Journal of Information Technology, 2021)
The learning system is the most important role in education. MIN Toweren has problems in the thematic learning system in mathematics. Students have poor learning motivation in class. Analysis of the learning system at MIN Toweren was carried out to find its weaknesses. With the SDLC system development method, a digital learning system application was built. The test results using blackbox testing and whitebox testing methods show that the application of the learning system is able to run well and functionally. Keywords: SDLC, learning system, MIN Toweren